Therapeutic Application of Cardiac Stem Cells and Other Cell Types. (26th June 2013) - Hayashi, Emiko; Hosoda, Toru
Abstract : Various researches on regenerative medicine were carried out experimentally, and selected modalities have been introduced to the clinical arena. Meanwhile, the presence of resident stem cells in the heart and their role in physiological cell turnover were demonstrated. So far skeletal myoblasts, bone marrow-derived cells, mesenchymal stromal cells, and resident cardiac cells have been applied for therapeutic myocardial regeneration. Among them, autologous transplantation of c-kit-positive cardiac stem cells in congestive heart failure patients resulted in an outstanding outcome, with long-lasting beneficial effects without major adverse events. By reviewing these clinical trials, an endeavor was made to seek for an ideal cellular therapy for cardiovascular diseases.